The Concept of Delegation of Local Government Authority (Study of Financial Supervision and Management) - TOLANG, Petrus Avelino Framayuka; DIBABA, Solomon Dessalegn (Protection: Journal Of Land And Environmental Law, 2024)
The development of regional autonomy has placed various new authorities possessed by the regions. One of these powers is the delegation of some regional authorities to sub-districts to support regional programs and policies. The sub-district itself has the authority, duties and functions, one of which is regarding financial management and supervision. The research method used is normative research with an approach to legislation. The results of the study show that the concept of delegating regional authority to sub-districts has been comprehensively regulated in Law Number 23 of 2014 concerning Regional Government. In the financial management and supervision of the sub-district, it is placed as a coordination line for the village in determining the APBDES which is regulated in PP Number 43 of 2014 Article 101 and Permendagri Number 113 of 2014 Article 23, namely the regent/mayor can delegate the implementation of the evaluation of the draft village regulation on APBDes to the sub-district head or other designations. In addition, the sub-district head has a role in submitting the APBDes Realization Report and the APBDes Realization Accountability Report to the regent/mayor.